The performance and physiological effects of caffeine and octopamine supplementation during endurance cycle exercise - Beaumont, R. (2017)
Caffeine consistently enhances endurance performance in temperate environmental conditions, while far less research has examined its ergogenic and physiological effects during prolonged exercise in the heat. Despite the performance benefit of an acute caffeine doses being less pronounced in regular caffeine users versus those not habituated to the drug, few studies have examined the influence of a prolonged period of controlled caffeine intake on endurance performance. The endogenous trace amine octopamine is purported to possess stimulant-like properties and influence fat metabolism, although no study has examined these effects in humans. The aim of this thesis was to further characterise the performance and physiological effects of caffeine during prolonged exercise, while elucidating a potential ergogenic role for octopamine. The first two studies investigated the ergogenic and thermoregulatory effects of low to moderate caffeine doses during prolonged cycle exercise in the heat. Chapter 4 demonstrated that 3 mg kg-1 caffeine, administered either as a single or split-dose (2 x 1.5 mg kg-1) before exercise, improved endurance performance without influencing thermoregulation during prolonged exercise at a fixed work-rate. Dividing the caffeine bolus appeared to confer an additional performance benefit, suggesting repeated low dose may potentiate the efficiency of the same total caffeine dose under these conditions. Chapter 5 demonstrated that a 6 mg kg-1 caffeine dose improved endurance cycle performance without differentially influencing thermoregulation than placebo. The level of habituation to caffeine influences the ergogenic effect of an acute dose, yet previous studies have employed sub-chronic supplementation protocols. Chapter 6 investigated the effect of a twenty-eight day supplementation period on endurance cycle performance. Habituation to caffeine attenuated the ergogenic effect of an acute caffeine dose, without any change in circulating caffeine, substrate oxidation or hormonal concentrations. In chapter 7 the performance and metabolic effects of octopamine was investigated. Octopamine supplementation did not influence performance, hormonal concentrations or substrate oxidation, likely due to low serum concentrations of the drug.